Mainstreaming Workshops for Vocational Administrators. Final Report - Dahl, Peter R.; American Institutes for Research in the Behavioral Sciences, Palo Alto, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
The document presents the final report of a project to develop mainstreaming workshops to help vocational administrators in California include handicapped students in their programs. Following a needs assessment survey of approximatey 500 vocational administrators, guides to material resources and support services were prepared and distributed at eight workshops which served 348 people. Among the workshop topics were: legal requirements for serving handicapped students, technical assistance available to vocational educators through the State Department of Education, preparing effective individual education plans, planning programs for handicapped students, getting students ready to function on the job, equipment and workplace design, strategies for assessing and placing handicapped students, and strategies for instructing handicapped students in mainstream classrooms. Over 98% of those completing end of workshop questionnaires felt that the workshop would be helpful in their work. Over 80% gave one of the two most favorable responses (of four possibilities) in assessing workshop content and organization. (Author/DLS)
Sponsoring Agency: Bureau of Occupational and Adult Education (DHEW/OE), Washington, DC. Div. of Research and Demonstration.
Contract Number: G007702227.
ERIC Note: Two documents previously entered in ERIC have been removed. Citations on title pages in Appendixes.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrators; Disabilities; Individualized Instruction; Legislation; Mainstreaming; Program Development; State Programs; Student Evaluation; Student Placement; Vocational Directors; Vocational Education; Workshops; California; Reports, Descriptive